(untitled) (Journal of Rangpur Medical College, 2024)
Background: Malnutrition, a subacute or chronic state, were prevalent among oral squamous cell carcinoma (OSCC) patients, may impair immune function, increase susceptibility to infection and increase complications of the treatment, thus leading to an increased mortality of cancer patients Objective: To evaluate the nutritional status of patients with oral squamous cell carcinoma and its association with post-operative wound dehiscence. Methods: The prospective study involved 60 patients with oral squamous cell carcinoma carried out from 1st January to 31st December 2020 in Oral & Maxillofacial Surgery Department of Bangabandhu Sheikh Mujib Medical University and Dhaka Dental College & Hospital, Dhaka, Bangladesh, divided into 2 groups; Group-I: patients who developed no post-operative complications (n=49) and Group-II: patients who developed post-operative wound dehiscence (n=11).Nutritional assessments were performed on the day prior to operation using four parameters (BMI, percent ideal body weight, serum albumin, total lymphocyte count) classifying the patient’s nutritional status into normal nutrition, mild malnutrition, or moderate malnutrition, then the patients were followed up till discharge and post-operative wound dehiscence was recorded. Statistical analysis was performed using SPSS version 23 considering p-value <0.05 as significant. Results: Nutritional assessments based on four nutritional indicators revealed that malnutrition was significantly associated with patients who developed post-operative wound dehiscence compared to patients who developed no post-operative complications (Group-I vs Group-II : mean BMI 21.3±2.2 vs 17.1±1.4(p=0.001);mean percent ideal body weight 97.0±11.4 vs 81.6±6.5(p=0.001); meanserum albumin 33.6±4.1vs 26.9±4.2gm/d (p=0.001); meantotal lymphocyte count 2282.6±819.1 vs 1736.0±474.8 mm3, (p=037). Conclusion: Malnutrition is associated with post-operative wound dehiscence in patients with oral squamous cell carcinoma. So, every patients houldassess nutritional status pre-operatively to reduce post-operative complecations. J Rang Med Col. September 2024; Vol. 9, No. 2: 33-37